Makueni County Resource Hub - CGIAR Research Program on Water, Land and Ecosystems (2021)
The Makueni Resource Hub was co-developed with stakeholders from the Makueni county government and officially launched at the Kenya Devolution Conference in November 2021. It has been embedded into county decision-making processes across multiple departments (agriculture, environment, planning, education and health).